The Politics of Teaching Islamic Law(Shariah) in the Institutions of Legal Education in Pakistan with Special Reference to the Colonial Legacy - Dr. Muhammad , Dr. Muhammad (Al-Amīr Research Journal for Islamic Studies, 2024)
This research paper examines the teaching of Islamic law (Shariah) in the legal education system in Pakistan with special focus on colonial origin and its impact on contemporary legal education and profession. The study relates the importance of British-Indian Common Law as the backbone for legislation of Pakistan but also mentions about the Islamization of certain laws, which means laws must be practiced in line with the Holy Quran and the Sunnah which demonstrates the significance of learning Islamic law in legal education. The paper also outlines the differences between the Madrasas’ curriculum and teaching process from that of a University in the teaching of Islamic law. It critiques the current legal education system for ignoring Islamic law and jurisprudence and making the lawyers and judges unable to analyze the modern legal issues in the light of Islamic jurisprudence. The findings indicate that colonial systems have had a significant impact on modern educational approaches, resulting in a lack of critical engagement and grasp of Islamic law. The paper advocates for a decolonized curriculum that encompasses in-depth knowledge of Islamic law, fosters critical thinking, and links legal education to the socio-legal needs of the Islamic Republic of Pakistan. Keywords: Shariah, Subject, Legal Education, Syllabus, Pedagogy, Curriculum, Colonial Era, etc.